Perceiving gender locally, globally, and intersectionally - Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Advances in gender research ;, 2009)
The introduction and 10 essays in this volume address questions about how feminist scholars conceptualize gender and view it in relationship to other attributes of individuals and of social systems. The authors strive for intersectional analyses broadening that approach beyond the gender, race and class paradigm to include sexuality, employing a variety of methodologies, and arguing that intersectionality is, or should be, not just theory, but praxis as well. The topics include the empowerment of women globally; the relationship of gender to international migration; gender differences in organizational participation; heteronormativity in organizations and in the media; the ways that the global affects the local in legislation, the workplace and the academy; the relationship between positive stereotypes of women and support for women's rights; and essentialist themes in men's movements. The discussions of globalization and empowerment and of migration are explicitly transnational in perspective. The remaining essays analyze data gathered in particular locations, but all have broader implications. Three nation-specific essays focus on organizational participation in Brazil, feminism in the Canadian academy, and sexual harassment legislation in Japan. Those on the media, social movements and voluntary organizations, and on modern prejudice are based on data from the United States. All of the authors and co-authors, whether professors emerita or graduate students, are trained in the social sciences. Nevertheless, the essays reflect the increasingly interdisciplinary approach to data and methods that characterizes contemporary feminist writing and research.